2000
DOI: 10.1243/0309324001514008
|View full text |Cite
|
Sign up to set email alerts
|

Piping elbows with cracks Part 2: Global finite element and experimental plastic loads under opening bending

Abstract: Experimental and finite element (FE) plastic load results of cracked piping elbows under opening in-plane bending are presented and compared with data from similar defect-free components. The elbows used were short-radius components with an outside diameter of 88.9 mm and thickness 5.49 mm. Axial (at the crown) and circumferential (at the intrados) blunt crack-like defects were produced using electric discharge machining (EDM) procedures. Both short (è 218 axial or 2â 468 circumferential) and long (è 758 axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 2 publications
0
35
0
Order By: Relevance
“…These tensile tests, on what was a typical carbon steel piping material, indicated that a clear, perfectly plastic behaviour existed with a`flat region' up to strain levels approaching 2 per cent, beyond which strain hardening occurred (see Fig. 2 of Part 2 [9]). …”
Section: Scope Of the Investigationmentioning
confidence: 94%
“…These tensile tests, on what was a typical carbon steel piping material, indicated that a clear, perfectly plastic behaviour existed with a`flat region' up to strain levels approaching 2 per cent, beyond which strain hardening occurred (see Fig. 2 of Part 2 [9]). …”
Section: Scope Of the Investigationmentioning
confidence: 94%
“…1 [6][7]. Carbon steel bends with an outer diameter (Do) of 400mm and a nominal thickness (tnom ) of 20mm were used.…”
Section: Collapse Moment Calculation Using Finite Element Analysesmentioning
confidence: 99%
“…These parameter sets are believed to cover the practically relevant range of elbows in the power generating industry. The length of the attached straight pipe is chosen to be ten times the pipe mean radius, L ¼ 10r, which is sufficiently long to avoid end effects due to the applied loading [16][17][18][19][20][21]. Both circumferential part-through surface and through-wall cracks were considered.…”
Section: Geometrymentioning
confidence: 99%
“…[11][12][13][14]). For cracked elbows, several researchers performed both experimental and numerical works to investigate the effect of cracks on plastic limit loads [15][16][17][18][19]. The authors also proposed closed-form approximations of plastic limit loads for circumferential cracked elbows under in-plane bending, via small strain three-dimensional (3-D) finite element (FE) limit analyses using elasticperfectly plastic materials [20,21].…”
Section: Introductionmentioning
confidence: 99%